A contação de histórias como possibilidade auto(trans)formativa com professoras - Oliveira, Marilei Almeida de (2023)
This Professional Master's research is part of the Pedagogical Management and Educational Contexts Research Line, of the Graduate Program in Public Policies and Educational Management at the Federal University of Santa Maria/RS. With it, we seek to tell stories, our stories and those of other people who join us in studies, reflections and propositions about storytelling as a self-(trans)formative approach, capable of contributing as a possibility in the process of welcoming and space-time of permanent self(trans)formative processes with early childhood education teachers in the municipality of Santa Maria/RS. The main objective of this research was to understand how storytelling can be carried out in a self-(trans)formative approach that contributes/welcomes mentally and emotionally fragile teachers in the municipal network of Santa Maria/RS. In addition, to raise awareness and carry out the self(trans)formation research with the co-authors, we adopted the political-epistemological proposal of the Investigativeauto(trans)formative Dialogical Circles (HENZ, 2015), as a possibility for each one to say their word and as a process of permanent self(trans)formation with the participating teachers. We developed 04 face-to-face meetings with early childhood education teachers from the western region of Santa Maria/RS; in addition to dialogues, sharing of formative moments and the organization of a questionnaire with specific questions raised in the Circles. Studies carried out individually and also shared with the teachers made us understand, know and (re)know that democratic management and permanent self(trans)formation with teachers are viable for a hopeful path in which we want to assume our pedagogical and political commitment as professionals, humans and participants in the construction of a democratic and just society. Through the awareness brought about by the dialogical-reflective space-times, we feel challenged to commit to being a protagonist in the struggle for an education of social and human quality, with dialogued and participatory praxis, at the service of the liberation and humanization of professional teachers as well. In this sense, based on the circles and other dialogical-reflective space-times, we identified points in common with the teachers' emotional and mental illness/exhaustion; as well as, we delimit points related to the welcoming of these teachers and, in view of this scenario, together, we seek to understand how storytelling emerges as a possibility to soften these indices, through Auto(trans)formative processes. The dialogues and systematization of the intervention construct (“final product”) consists of presenting storytelling as a permanent self(trans)formative approach for early childhood education teachers in the municipal network of Santa Maria/RS, an explanatory document containing the experiences and the possibilities of new training processes, based on storytelling, which will be shared with the municipality's education department and schools, seeking to contemplate the theoretical-practical constructs of the entire process of this research and organize ways of welcoming fragile teachers/emotionally and mentally ill.